Changes in physical developement and body built of candidates to academy of physical education from 1953 to 1973 - Drozdowski, Zbigniew (Anthropological Review, 1974)
Summing up works carried on the material concerning physical developement of candidates to Academy of Physical Education in Poznań, the author have found:1) the level of physical developement in investigated group during the last 20 years was increasing except the last few years when it become stabilized without significant variations; 2) in body built most frequent are traces of element V, less frequent — A; 3) candidates to Academy of Physical Education represent selected somatic group as compared with groups of average individuals or another groups of students.